2017
DOI: 10.1111/1346-8138.14106
|View full text |Cite
|
Sign up to set email alerts
|

Generalized eruptive keratoacanthoma with vitiligo followed by the development of prurigo nodularis: A case report and published work review

Abstract: Herein, we report a unique case of generalized eruptive keratoacanthoma (GEKA) in a 47-year-old Chinese man presenting with extensive pruritic papules and nodules accompanied by oral lesions. He also had a 2-year history of vitiligo and long-term experience of working outdoors. Biopsies were consistent with keratoacanthoma . Interestingly, prurigo nodularis (PN) was found in histopathology at 1-year follow up. To our knowledge, this is the first report describing a case of GEKA with oral lesions complicated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Patients diagnosed with PN exhibit a high prevalence of celiac disease, Hashimoto thyroiditis, inflammatory bowel diseases, and type 1 diabetes mellitus [126][127][128]. A US epidemiologic study confirmed an increased rate of celiac disease in PN patients (OR 2.70, 95% CI 1.43-5.08) and identified associations with inflammatory bowel diseases, including Crohn's disease (OR 2.40, 95% CI 1.51-3.81), ulcerative colitis (OR 1.64, 95% CI 1.13-2.37), and type 1 diabetes mellitus (OR 2.23, 95% CI 1.72-2.90) [13].…”
Section: Clinical Features Diagnosis and Comorbiditiesmentioning
confidence: 99%
“…Patients diagnosed with PN exhibit a high prevalence of celiac disease, Hashimoto thyroiditis, inflammatory bowel diseases, and type 1 diabetes mellitus [126][127][128]. A US epidemiologic study confirmed an increased rate of celiac disease in PN patients (OR 2.70, 95% CI 1.43-5.08) and identified associations with inflammatory bowel diseases, including Crohn's disease (OR 2.40, 95% CI 1.51-3.81), ulcerative colitis (OR 1.64, 95% CI 1.13-2.37), and type 1 diabetes mellitus (OR 2.23, 95% CI 1.72-2.90) [13].…”
Section: Clinical Features Diagnosis and Comorbiditiesmentioning
confidence: 99%